2005
DOI: 10.1080/01485010590919666
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Expression in the Testicular Tissue of Fertile and Infertile Men

Abstract: There have been several studies about the presence of leptin in serum and testicular tissue, and none of them compares the leptin expression in the testicular tissue of fertile and infertile men. We assessed the presence of leptin expression in the testicular tissue of fertile and infertile men. 20 azoospermic infertile men were included in the study. All patients underwent testicular sperm extraction (TESE) for ICSI. For the detection of leptin, the immunohistochemistry was carried out. Intensity of immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In contrast, in the mouse, leptin and its receptor were detected exclusively in germ cells of immature and mature testes (El-Hefnawy et al, 2000;Herrid et al, 2008). Furthermore, in the human adult testes, leptin was found in seminiferous tubules, whereas Ob-R was detected in Leydig cells (Glander et al, 2002;Soyupek et al, 2005;Ishikawa et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, in the mouse, leptin and its receptor were detected exclusively in germ cells of immature and mature testes (El-Hefnawy et al, 2000;Herrid et al, 2008). Furthermore, in the human adult testes, leptin was found in seminiferous tubules, whereas Ob-R was detected in Leydig cells (Glander et al, 2002;Soyupek et al, 2005;Ishikawa et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…In fact, Lep and/or Ob-R were detected in rodent testes (Caprio et al, 2003;El-Hefnawy et al, 2000;Herrid et al, 2008), in human testes and seminal plasma (Glander et al, 2002;Soyupek et al, 2005;Ishikawa et al, 2007), in human sperm (Aquila et al, 2005), in boar sperm (De Ambrogi et al, 2007), and in pig sperm (Aquila et al, 2008). Furthermore, a recent paper reported the effects of leptin treatment, alone or in combination with dietary energy restriction, on different reproductive parameters of male rats (Sirotkin et al, 2008).…”
mentioning
confidence: 99%
“…This discrepancy may be due to interspecies difference. LEP and OBR were found in human seminiferous tubules (Soyupek et al 2005), human seminal plasma (Jope et al 2003), human sperm and, recently, OBR was also identified in boar sperm (De Ambrogi et al 2007). In the present study, we investigated LEP and OBR expression in pig sperm, evaluating their potential role on sperm capacitation and survival.…”
Section: Introductionmentioning
confidence: 99%
“…It has central roles in the energy expenditure, food intake, many reproductive processes, regulation of energy homeostasis, neuroendocrine function, and metabolism (Kelesidis et al, 2010). Beside the synthesis by adipose tissue as the main source (Go et al, 2013), there have been indentified other sources of leptin in the body including testicles (Soyupek et al, 2005), ovaries (Löffler et al, 2001), placenta (Maymó et al, 2011), cartilage and bone cells (Morroni et al, 2004), skeletal muscle (Solberg et al, 2005) and stomach (Mix et al, 2004). Furthermore, the mitogenic, transforming or migration-induced properties of leptin have been revealed in many different cell types such as smooth muscle cells (Oda et al, 2001), normal and neoplastic colon cells (Hardwick et al, 2001;Liu et al, 2001); and also normal and malignant mammary epithelial cells (Dieudonne et al, 2002;Laud et al, 2002).…”
Section: Introductionmentioning
confidence: 99%